Handlettering und moderne Kalligrafie für Einsteiger - Safarik, Natascha (Mitp Verlag, 2023)
Learn to write beautiful lettering from scratch Detailed step-by-step instructions for all letters Numerous alphabets for your own lettering projects Use of pencil, colored pencil, pointed pen and brush pen Do you see beautiful lettering and hand lettering everywhere and don't really dare to do it yourself? Or have you already taken the first steps but haven't quite got the hang of it yet? With this book you will learn hand lettering and modern calligraphy from scratch - easily and step by step. The book is particularly suitable for beginners, even if you think you can't write beautifully. You will learn all the basics of hand lettering and modern calligraphy that you need to be able to implement your own artistic lettering projects. First, the author explains the most important terms of letter anatomy and you will receive detailed information about the material, i.e. your writing tools as well as ink and paper. The author then shows you how to write different scripts and alphabets. You will learn the structure of the letters and fonts step by step and work with pencil, colored pencil, brush pen and pointed pen. With the alphabets in the book you get many examples to practice and for your own creative use.